HARNESSING CLASSICAL MUSIC TO IMPROVE READING COMPREHENSION: AN EMPIRICAL STUDY ON HIGHER EDUCATION STUDENTS - Afif Zuhdy Idham; Fibri Indira Lisanty AD (Adisam Publisher, 2026)
Advanced reading comprehension is a critical competency required for university students to achieve academic success; however, many undergraduates experience cognitive overload and anxiety when interacting with dense academic texts. This study empirically investigates the efficacy of utilizing a classical music background as an environmental intervention to improve reading comprehension among higher education students. Employing a quantitative approach with a quasi-experimental pre-test and post-test design, this study involved 70 undergraduate students who were equally distributed into an experimental group (n = 35), exposed to low-intensity non-lyrical classical music (60–80 bpm) during reading tasks, and a control group (n = 35), situated in a traditional silent classroom. Data were gathered through standardized academic reading tests and analyzed using descriptive and inferential statistics via SPSS. The descriptive results revealed that while both cohorts shared a homogenous baseline in the pre-test, the experimental group achieved a substantial post-test mean score increase (M = 82.10, Gain = +16.70) compared to the modest progress of the control group (M = 71.30, Gain = +6.50). Furthermore, the Independent Samples t-test confirmed a statistically significant difference in post-test performance between the two groups, t(68) = 4.21, p < .001. Grounded in the Arousal-Conjecture and Cognitive Load theories, these findings demonstrate that a structured acoustic environment successfully mitigates mental fatigue and optimizes working memory capacity. This study concludes that harnessing classical music is a viable, evidence-based pedagogical strategy to foster advanced literacy in modern tertiary education.